Pengaruh Pendapatan Asli Daerah, Dana Perimbangan Dan Belanja Modal Terhadap Pertumbuhan Ekonomi (Studi Kasus Provinsi di Indonesia Tahun 2018) - Larisa Dea Chatira; Ronny Malavia Mardani; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract The purpose of this study is to determine the effect of Regional Original Revenue, Balancing Funds, and Capital Expenditures on Economic Growth. The variables used in this study are Regional Original Revenue (x1), Balancing Funds (x2), Capital Expenditures (x3) and Economic Growth (y). The population and sample in this study were all provinces in Indonesia in 2018 as many as 34 provinces. This research uses explanatory research type. Data testing techniques used in this study are multiple linear regression testing techniques. The results of the analysis of this study indicate that Regional Original Revenue has a positive effect on Economic Growth, while the other two variables such as the Balancing Fund negative affect Economic Growth, and Capital Expenditures also negative affect Economic Growth.Keywords : Regional Original Revenue, Balancing Funds, Capital Expenditures, Economic Growth.